2003
DOI: 10.1080/01140671.2003.9514256
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of phenolic compounds in host resistance againstBotrytis cinereainleaves of the two commercially important kiwifruit (Actinidia chinensisandA. deliciosa) cultivars

Abstract: New Zealand Journal of Crop and Horticultural Science, 2003, Vol. 31: 221-233 Abstract Expression of phenolic compounds associated with constitutive and wound-induced resistance to Botrytis cinerea was studied in leaves of two kiwifruit cultivars, Actinidia chinensis 'Hort16A' and A. deliciosa 'Hayward'. Constitutive leaf resistance to B. cinerea was much greater in 'Hort16A' than in 'Hayward'. This resistance might be attributable, in part, to phenolic compounds, since phenolic extracts from non-induced 'H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 29 publications
1
25
0
Order By: Relevance
“…Results on phenols were hard to compare with literature values because of the poor information existing on kiwifruit that mainly reports the leaf or mature fruit phenolic composition and associated with anti-fungal activity (Ippolito et al 1997, Greaves et al 2001, Wurms et al 2003. In general, excepting for the epicatechin of shaded fruitstalks and flavonols of berry, the pattern of phenolic compound changes showed a decrease within the early weeks after fruit-set.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Results on phenols were hard to compare with literature values because of the poor information existing on kiwifruit that mainly reports the leaf or mature fruit phenolic composition and associated with anti-fungal activity (Ippolito et al 1997, Greaves et al 2001, Wurms et al 2003. In general, excepting for the epicatechin of shaded fruitstalks and flavonols of berry, the pattern of phenolic compound changes showed a decrease within the early weeks after fruit-set.…”
Section: Discussionmentioning
confidence: 97%
“…This is the case with kiwifruit phenolic compounds. Extensive studies have been made on phenolic composition in the leaf and the mature fruit (Ferguson 1984, Ippolito et al 1997, Greaves et al 2001, Wurms et al 2003 as well as on the juice (Dawes & Keen 1999). These studies gave more emphasis to their health protective role against oxidative damage to the human cell (Chun et al 2005, Park et al 2006.…”
Section: Introductionmentioning
confidence: 99%
“…Phenolic compounds were extracted by the Daayf et al (1997) procedure, modified for kiwifruit tissue as described by Wurms et al (2003), except that the aqueous phase containing conjugated phenolics was hydrolysed for 10 min (stem plug extracts) or 15 min (pericarp extracts) at 100°C in 2N HCl. Of the two phenolics fractions (free phenolics and acidhydrolysed phenolics) produced by this method, our analysis focused only on the acid-hydrolysed fraction, because earlier studies have demonstrated that this accounts for the majority of the anti-microbial activity (Daayf et al 1997;Wurms et al 2003).…”
Section: Phenolics Extraction and Separationmentioning
confidence: 99%
“…Of the two phenolics fractions (free phenolics and acidhydrolysed phenolics) produced by this method, our analysis focused only on the acid-hydrolysed fraction, because earlier studies have demonstrated that this accounts for the majority of the anti-microbial activity (Daayf et al 1997;Wurms et al 2003).…”
Section: Phenolics Extraction and Separationmentioning
confidence: 99%
See 1 more Smart Citation